Solidaritas Sosial Suku Dayak Tomun pada Ritual Tiwah di Desa Parit Kabupaten Kotawaringin Timur - Milda; Budhi, Setia (Huma: Jurnal Sosiologi, 2025)
Parit Village is a village that still maintains traditional values and carries out traditional rituals, one of which is Tiwah as a form of respect, expression of gratitude to ancestors, and the beliefs of the community. This research aims to analyse the value of social solidarity contained in the Tiwah ritual of the indigenous people of Parit Village. This research uses a qualitative approach with the type of field research conducted in Parit Village, Cempaga Hulu District, East Kotawaringin Regency. Data were collected through observation, interviews, and documentation, then the data were analysed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the Tiwah ritual performed by the indigenous people of Parit Village is a form of respect for ancestors. This ritual includes various activities such as buffalo slaughtering, bone removal, and making sandung and sapundu in the death ceremony. This research reveals that the Tiwah ritual has social and cultural meanings. The social meaning includes the building of mechanical solidarity, where this ritual strengthens family and social relations through mutual cooperation and cooperation between community members who have similar values and beliefs. The cultural meaning contained in the Tiwah ritual is a hereditary tradition from Kaharingan ancestors that functions as a form of human self-purification. Based on the Gemeinschaft theory, this ritual reflects social ties that are established on the basis of close personal and familial relationships. The research is expected to be a reference for future studies that explore the social solidarity of the Parit Village community using other approaches or theories, such as symbolic interaction theory or structuration theory, to complement the understanding of the social and cultural dynamics involved in the Tiwah ritual.